Pengaruh Modifikasi Perilaku Penghapusan (Extinction) Pada Perilaku Membanting Pintu & Melempar Barang Saat Marah Pada Anak Usia 5-6 Tahun - Isna Umroatul Farihah; Ari Purnomo Endah Aflahani (JURNAL LENTERA ANAK, 2021)
Early childhood is a child who is just learning to know himself, including his emotional social. At this time they are also new to feeling happy, sad, angry, disappointed and so on. Most young children are still not able to manage and express their emotions properly. This condition is caused by many factors such as children's communication, parenting patterns and children's environment. For this reason, behavior modification is used as a strategy to overcome deviant behavior in children. There are many methods, approaches, concepts and techniques that can be used in behavior modification. Extinction is also a strategy to stop reinforcement of inappropriate or inappropriate behavior. This is because many inappropriate behaviors are maintained due to positive reinforcement for these behaviors. This study aims to determine the effect of a behavior modification program to reduce the behavior of slamming doors and throwing things when angry with the elimination method (extinction). This study uses a case study method with a single subject, so that the effects of the modifications that have been given can be evaluated properly. The data collection method used in this study was interviews accompanied by observation. The subjects in this study amounted to one person, aged 5 years 5 months, and experienced non-adaptive behavior, namely slamming doors and throwing things when angry. The results of this study indicate that the behavior modification program with the elimination method to reduce the subject's behavior can be said to be successful. Changes in the frequency of behavior slamming doors and throwing things decreased significantly. Even though until now the subject sometimes still wants to throw things when angry even though in the end he puts the things back. This is because parents are less strict in applying the rules at home. This change in the subject's bedwetting behavior which is quite good is inseparable from the role of parents who are willing to assist researchers in implementing the rules for implementing this behavior modification at home.